Patient Safety Culture Instrument: A Systematic Review - Lestari, Eni Puji; Triharini, Mira; Qur'aniati, Nuzul (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2023)
The instruments of Hospital patient safety culture are connected to organizational culture aspects. This study aimed to review and synthesize knowledge and explore various instruments to measure hospital patient safety culture. Articles from 2018 to 2022 were selected from Web of Science, Sage Journals, SpringerLink, and Scopus. The terms used were patient safety culture, safety culture, clinical supervision, web-based, electronic, and technology. The selection procedure was managed by PRISMA 2020, and the inclusion and exclusion criteria were determined using PICO. 2.120 articles were found after duplicates were eliminated and the titles, abstracts, and keywords began to be checked.  After excluding an irrelevant study, only ten publications remained on assessing patient safety culture in hospitals. The prevailing definitions highlight patient safety culture as managing values, beliefs, attitudes, and competencies within a healthcare organization, influencing member behavior and the approach to errors, reporting, and learning. It aims to reduce and prevent unintended patient harm through various mechanisms and tools tailored to fit each institution's values. Paper-based or electronic-based instruments have advantages because they were created and utilized in numerous investigations. The survey response rate is also influenced by how healthcare personnel view the culture surrounding patient safety.  This research is crucial for hospitals and the broader healthcare community as it equips them with the knowledge and tools needed to cultivate a culture of patient safety, reduce errors, and ultimately protect the well-being of patients. It addresses the evolving healthcare landscape, emphasizing customization, technology, and staff involvement in pursuing safer healthcare environments.   Keywords: Hospital, instruments, patient safety culture